2020
DOI: 10.1002/rmb2.12325
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of subclinical hypothyroidism and the potential contribution to miscarriage: A review

Abstract: Background There is no clear cutoff value for thyroid‐stimulating hormone (TSH) level that defines subclinical hypothyroidism (SCH). Moreover, TSH levels can be affected by numerous factors. Although mild SCH has been implicated in miscarriage, the relationship between TSH levels and miscarriage remains unelucidated. Methods We reviewed nine known risk factors affecting TSH levels and 28 studies investigating the potential association between mild SCH and miscarriage, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 109 publications
0
1
0
1
Order By: Relevance
“…well-established evidence that women with hyperthyroidism during pregnancy should be treated, as studies have shown that untreated hyperthyroidism may increase the risk of miscarriage [44]. Additionally, the risk of miscarriage has an association with the serum TSH level [45], suggesting that medical personnel should regularly monitor TSH levels in pregnant women to reduce the incidence of adverse pregnancy outcomes. It may be necessary to further study this issue to reveal whether ATDs treatment can improve other pregnancy outcomes of hyperthyroidism women [46].…”
Section: Plos Onementioning
confidence: 99%
“…well-established evidence that women with hyperthyroidism during pregnancy should be treated, as studies have shown that untreated hyperthyroidism may increase the risk of miscarriage [44]. Additionally, the risk of miscarriage has an association with the serum TSH level [45], suggesting that medical personnel should regularly monitor TSH levels in pregnant women to reduce the incidence of adverse pregnancy outcomes. It may be necessary to further study this issue to reveal whether ATDs treatment can improve other pregnancy outcomes of hyperthyroidism women [46].…”
Section: Plos Onementioning
confidence: 99%
“…Повышенная выработка ТТГ часто является ответом организма беременной на поздний гестационный возраст, ожирение, длительность климатического сезона с низкой температурой воздуха, стимуляцию яичников [9]. Дисфункцию щитовидной железы в период гестации также связывают с возникновением относительного дефицита йода, подавлением функции аденогипофиза и снижением уровня тиреотропина за счет усиленной секреции хорионического гонадотропина человека (ХГЧ), повышением уровня эстрогена, концентрации сывороточного тироид-связываю щего глобулина в сыворотке, дейодированием тироксина под влиянием плаценты [6,10].…”
Section: Introductionunclassified